Synthesis of zinc oxide-doped reduced graphene oxide (rGO) nanocomposites on visible light-driven photocatalytic and antibacterial activity applications - Pham Thi Thuy; Bui Thi Cam Hue; Nguyen Xuan Sang; Le Thi Thanh Thuy; Phuoc Long Lieu (Nano Express)
In this study, reduced graphene oxide (rGO), ZnO nanocomposites, and zinc oxide-doped reduced graphene oxide (ZnO/rGO) nanocomposites were successfully synthesized via the sol–gel method and investigated for the removal of methyl blue (MB) dye and antibacterial activity under visible light irradiation. The synthesized nanocomposites were characterized using XRD, SEM, EDX, FTIR, UV–vis DRS, and BET techniques to analyze the crystallographic structure, phase, surface morphology, and different functional groups in the prepared catalysts. The ZnO/rGO nanocomposites demonstrated a great photocatalytic performance over 98% degradation of 20 mg L ^−1 of methylene blue (MB) dye within just 90 min under visible light. A heterojunction material achieved a higher 20% than that of the ZnO single-phase. Among the prepared photocatalysts, the nanocomposite with 0.2 grams rGO demonstrated the best results. Reusability studies revealed that ZnO/rGO catalysts maintained over 90% efficiency up to three cycles, with rGO serving as an effective adsorbent and ZnO providing catalytic activity. In addition, the antibacterial activity of the nanocomposites was evaluated against both Gram-positive and Gram-negative bacteria, showing significant inhibition due to the photocatalytic generation of reactive oxygen species. These findings suggest that ZnO/rGO nanocomposites are promising materials for environmental remediation and antibacterial applications.